The Revolution Of Mobile Services In Malaysia: A Case Study On AKN Messaging Technologies Berhad (AKN MTECH) - Chan, Pey Chiun (2008)
This case study is onhow AKN MTech outstand other Content Providers as the pioneer in the mobile messaging industry,launching value-added products and services and forming partnerships with mobile operators.